2008
DOI: 10.1016/j.semcdb.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila follicle cells: Morphogenesis in an eggshell

Abstract: Epithelial morphogenesis is important for organogenesis and pivotal for carcinogenesis, but mechanisms that control it are poorly understood. The Drosophila follicular epithelium is a genetically tractable model to understand these mechanisms in vivo. This epithelium of follicle cells encases germline cells to create an egg. In this review, we summarize progress toward understanding mechanisms that maintain the epithelium or permit migrations essential for oogenesis. Cell-cell communication is important, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 180 publications
1
146
1
1
Order By: Relevance
“…These developmental processes are essential for constructing the eggshell and establishing the body axes of the egg and resultant embryo, thereby being crucial for the egg development. We have previously shown that lethal (2) giant larvae (lgl), a Drosophila neoplastic tumor suppressor gene (nTsG) is required for the posterior follicle cell (pFc) fate induction during antero-posterior pattern formation of the follicular epithelium. In this report, we further characterize lgl in this epithelium patterning and the morphogenetic changes of specified border cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These developmental processes are essential for constructing the eggshell and establishing the body axes of the egg and resultant embryo, thereby being crucial for the egg development. We have previously shown that lethal (2) giant larvae (lgl), a Drosophila neoplastic tumor suppressor gene (nTsG) is required for the posterior follicle cell (pFc) fate induction during antero-posterior pattern formation of the follicular epithelium. In this report, we further characterize lgl in this epithelium patterning and the morphogenetic changes of specified border cells.…”
Section: Resultsmentioning
confidence: 99%
“…1 These specified FCs subsequently undergo a series of morphogenetic changes aimed at forming the complex eggshell. 1,2 Among morphogenesis of the follicular epithelium, the border cell migration is a well-studied model system for elucidating how the collective cell movement in development is regulated. 3,4 Numerous studies have shown that the collective and guided border cell migration requires a number of coordinated signaling activities such as JAK/STAT, JNK, PVR pathways and ecdysone signaling etc.…”
Section: Introductionmentioning
confidence: 99%
“…2 e). Specialized follicle cells called anterior polar cells (Wu et al, 2008) recruit six to eight adjacent follicle cells to form the migratory border cell cluster (Montell et al, 1992), which detaches from the follicular epithelium and migrates in between the nurse cells to eventually reach the anterior dorsal border of the oocyte (Fig. 2 e; Rørth, 2002;Montell, 2003), where they will form a structure necessary for sperm entry, the micropyle.…”
Section: Polarization Of the Collective: Leaders And Followersmentioning
confidence: 99%
“…In particular, there has been extensive research on egg development, because oogenesis provides a tractable way to investigate many different developmental processes, including tissue patterning, cell polarity changes, cell cycle switching, and translational regulation 1,2,3,4 . One important morphogenic event during oogenesis is the specification, acquisition of motility, and migration of a set of cells called border cells (reviewed in 5 ).…”
Section: Introductionmentioning
confidence: 99%